Functional status and well being in chronic obstructive pulmonary disease with regard to clinical parameters and smoking: a descriptive and comparative study. Issue 8 (August 1996) - Engström, C. P.; Persson, L. O.; Larsson, S.; Rydén, A.; Sullivan, M.
Abstract : BACKGROUND: Self-assessment questionnaires which measure the functional and affective consequences of chronic obstructive pulmonary disease (COPD) give valuable information about the effects of the disease and may serve as important tools with which to evaluate treatment. METHODS: A cross sectional comparative study was performed between patients with COPD (n = 68), stratified according to pulmonary function, and a healthy control group (n = 89). A battery of well established clinical and quality of life measures (the Sickness Impact Profile (SIP), Mood Adjective Check List (MACL), and Hospital Anxiety and Depression scale (HAD)) was used to examine in which functional and affective aspects the patient group differed from the control group and how these measures related to pulmonary function and smoking habits. RESULTS: Compared with the controls, COPD affected functional status in most areas, not just those requiring physical activity. Forty six patients with forced expiratory volume in one second (FEV1) below 50% predicted showed particularly high levels of dysfunction in ambulation, eating, home management, and recreation/ pastimes (SIP). Despite this, their level of psychosocial functioning and mood status was little different from that of the healthy controls. Among the patients, a subgroup reported substantial psychological distress, but mood status was only weakly, or not at all, related to pulmonary function. Smoking habits did not affect functional status or well being. CONCLUSIONS: Quality of life is not significantly affected in patients with mild to moderate loss of pulmonary function, possibly due to coping and/or pulmonary reserve capacity. This suggests that generic self-assessment questionnaires are of limited value for detecting the early consequences of COPD. However, in later stages of the disease they are sensitive enough to discriminate between patients with different levels of pulmonary dysfunction. The low correlations between the indices of pulmonary function and the indices of affective status suggest that well being depends, to a large extent, on factors outside the clinical domain.